DIRECT STENTING VERSUS BALLOON PRE-DILATATION IN ELECTIVE PERCUTANEOUS CORONARY INTERVENTION - Shahzad, Khurram; Mallick, Nadeem Hayat; Amin, Shahid; Ahmad, Sajjad; Ullah, Hazrat (Journal of Ayub Medical College Abbottabad, 2020)
Background: Stents are now deployed in almost 95% of all percutaneous coronary interventions (PCIs). Recent advances in balloon and stent technology has improved the technique of direct stent (DS) strategy i.e., stent delivery without pre-dilatation instead of conventional stenting (CS), i.e., stent implantation after balloon pre-dilatation with multiple advantages. Methods: This randomized controlled trial was conducted at the Cardiology. Department, Punjab Institute of Cardiology, Lahore from April to September, 2017. One hundred patients who were being treated by percutaneous coronary intervention (PCI) were enrolled into two Groups e.g., Group I & group II. 50 patients undergoing direct stenting were enrolled in group I and 50 patients undergoing stenting after balloon pre-dilatation were enrolled in group II after randomization. All patients were treated by single type drug eluting or bare metal stents. Chi square test was used for association and t-test for mean difference between two groups in comparison to post dilatation, fluoroscopy time, procedure time, amount of contrast used, procedural success, side branch compromise, slow flow. The p-value of Ë‚ 0.05 was significant. Results This study consisted of 76 males and 24 females out of a total count of 100, with the average age of 52.2±0.01 years. Overall, 43 (43%) patients were diabetic and overall, 44 (44%) were hypertensive. Most of the patients 55 (55%) had PCI to LAD. Average fluoroscopy time 4.l±2.5 minutes in Group I was significantly lesser as compared to 6.7±3.8 minute group II (p-value <0.05). The average procedure time was also marginally lesser in Group I, 23.4±11.6 in comparison to the second Group 33.7±14 (p-value <0.05). Side branch compromise was observed in 10 (20%) in the first group as compared to 8 (16%) the second group. Conclusion: In comparison to stenting preceded by balloon pre-dilatation, direct stenting is a safer and more feasible procedure with respect to radiation exposure, cost and time duration of the procedure. Keywords: PCI; Coronary artery disease; Stenting directly; Balloon angioplasty